1997
DOI: 10.1016/s0735-1097(97)00142-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Follow-Up After Successful Repeat Percutaneous Intervention for Stent Restenosis

Abstract: In-stent balloon angioplasty for stent restenosis in native vessels seems to be an effective method in terms of a low long-term clinical event rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(84 citation statements)
references
References 30 publications
6
72
1
3
Order By: Relevance
“…These results suggested that the intrinsic apoptotic pathway was induced in VSMCs that were exposed to ultrasound. The proliferation and apoptosis of VSMCs play important roles in the pathologic restenosis of blood vessels after percutaneous transluminal angioplasty and stenting (Reimers et al, 1997). Therefore, ultrasound treatment may potentially be considered as a new therapeutic tool for intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that the intrinsic apoptotic pathway was induced in VSMCs that were exposed to ultrasound. The proliferation and apoptosis of VSMCs play important roles in the pathologic restenosis of blood vessels after percutaneous transluminal angioplasty and stenting (Reimers et al, 1997). Therefore, ultrasound treatment may potentially be considered as a new therapeutic tool for intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the increased proliferation and migration of VSMCs are undoubtedly required and potent for vascular repair (Beamish et al, 2010). However, the excessive proliferation of VSMCs can aggravate vascular injury, which was reported to occur in restenosis after angioplasty (Reimers et al, 1997). Therefore, it is important to find strategies to prevent the excessive proliferation or induce the apoptosis of VSMCs to a certain extent that does not compromise the normal cellular expansion.…”
Section: Introductionmentioning
confidence: 99%
“…21,28 Thus, in-stent restenosis is an important clinical problem. Restenosis after stent implantation is mainly caused by neointimal proliferation through the stent struts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that focal in-body restenosis (type Ic [7]) constitutes a more benign pattern of in-stent restenosis, which can be effectively treated using conventional angioplasty (7)(8)(9). Conversely, other types of restenosis that are more frequently associated with procedural issues (eg, geographic miss, in the case of type Ib restenosis) or with aggressive neointimal proliferation may benefit from repeat SES implantation.…”
Section: Treatment Of In-ses Restenosismentioning
confidence: 99%